Poverty, Inequality, and Unethical Behavior of the Strong - Hillman, Arye (IMF Working Papers; Working Paper ;, 2000)
This paper is concerned with economic consequences of unethical governance. A framework is set out, based on principles of Friedrich Nietzsche, that ties poverty and inequality to unethical behavior of the strong toward the weak. The paper contributes to an understanding of why poverty and inequality have remained entrenched in some societies in spite of repeated programs intended to improve living standards. The purpose is to include ethics of governance, and, in particular, unethical behavior of the strong toward the weak, in preconditions for economic development.